Evaluation of re-used medicinal leeches as a potential source for nosocomial MDR bacterial infections in canines - Soula, Mariajesus; Berke, Kara; Upchurch, David A.; Barbur, Laura A.; Huber, Abigail L.; Amachawadi, Raghavendra G. (Frontiers in Veterinary Science, 2025)
ObjectivesLeech therapy is commonly used in medicine as a treatment for venous congestion. Since a concern with reusing leeches is potential spread of infections, it is recommended to discard leeches after use. If a leech harbored bacteria from one patient in its gastrointestinal (GI) tract, it could transmit them to another patient, potentially, serving as a vector for multidrug resistant (MDR) infections. The objectives of this study were to determine if MDR Staphylococcus aureus can be transmitted from inoculated blood into a leech, how long can the bacteria can persist within the leech and its environment, and if leeches can transmit the bacteria during refeeding.Animals63 leeches were split into eight treatment groups and one control group.MethodsTreatment leeches were fed canine blood inoculated with an MDR strain of Staphylococcus aureus while control leeches were fed clean canine blood. Cultures were obtained at 1 day, 1 week, and 1-, 2-, 3- and 4-months post-inoculation. Culture samples were taken from the aquarium water, GI contents, and blood that the leeches were allowed to refeed on. Cultures were evaluated for the presence of Staphylococcus aureus.ResultsAll water samples were negative except for one tank at 7 days after feeding. After 2 and 3 months, all GI tracts and blood meal samples were negative, respectively.Clinical significanceLeeches will harbor MDR Staphylococcus aureus after inoculation. This bacterium is not detectable in the water after 7 days or in the leech and blood meal after 3 months. Further studies should be conducted to determine the reproducibility of these results given the novel complications identified throughout the course of our study.